Lab in Bag for Higher and Technical Education - Jolly, Lochan; Kaulgud, Sukruti; Mishra, B. K. (Journal of Engineering Education Transformations, 2025)
In order to generate future entrepreneurs capable of resolving challenges with the use of technology, institutions must implement programs that foster students’ holistic development. To facilitate holistic development of students, NEP 2020 emphasizes on collaboration, communication, research, problem solving, critical thinking, and creativity skills that students need to be successful in today’s world. NEP 2020 suggests to introduce blended learning environment which shows students the scientific method that can be applied to everyday life with emphasis on more practical oriented education unlike traditional science and math education. Students will become solution providers if they spend time in laboratories for experimentation and research. According to the current situation, higher and technical education curriculum provide limited time for practical work, and even if a student wishes to work extra during free periods, there are few resources available during working hours because there are very few labs and they are occupied with the regular curriculum conduct. Due to these limitations, students have fewer number of opportunities to discover solutions for real-world issues and applications. Access to the laboratory and laboratory equipment beyond working hours is the need of the hour. This is the reason for developing “Lab in Bag” to provide learning environment beyond working hours. Through these laboratory equipment’s, students will have access to a variety of hardware devices at home to explore and expand their knowledge. This will develop innovation and creativity in them. This philosophy can be achieved with the advantages of miniaturized and low-cost equipment and facilities. The focus of “Lab in Bag” is technical subjects involving hardware Experiments. The expected outcome of this setup is that it will provide students with a flexible platform which gives them opportunities to learn using reliable and economical setups. To measure performance of the “Lab in Bag” devices, experimentation is done using traditional equipment and equipment provided in Lab in Bag. This study explains that results with 0.002% error margin can be achieved with 30MHz-2Channel Oscilloscope and Digital Oscilloscope for Analog and Devices Electronics experiments. It further establishes positive correlation of flexibility, connectivity and reliability with usability. Positive correlation of these parameters shows that students are highly interested in using “Lab in Bag” for continuing research and innovation.